The Effect of Gamification-Based Educational Games on Improving Students’ Motivation and Quality of Mathematics Learning in Junior High School - Anggi Virlanda; Eva Julyanti; Sakinah Ubudiyah Siregar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Gamification-based learning has been increasingly applied as an instructional strategy to enhance students’ engagement in mathematics learning. This study aimed to describe students’ learning motivation and learning quality after the implementation of gamification-based educational games in junior high school mathematics learning. A descriptive quantitative approach was employed involving seventh-grade students at MTs Amalianur Pematang Seleng. Data were collected using a learning motivation questionnaire and mathematics learning tasks integrated into gamification platforms, namely Quizizz and Kahoot. The data were analyzed using descriptive statistics, including mean scores, score distribution, and categorical interpretation. The results indicate that students’ learning motivation tends to fall within the high category, characterized by increased enthusiasm, active participation, and positive attitudes toward mathematics learning. In addition, students’ learning quality also demonstrates a positive tendency, as reflected in their ability to understand and solve mathematical problems presented through gamified learning activities. Overall, the findings suggest that gamification-based educational games can serve as a supportive instructional approach to foster students’ motivation and learning quality in mathematics classrooms. However, the results are limited to descriptive interpretation and do not imply causal relationships. Keywords: Gamification, Learning Motivation, Learning Quality, Mathematics